Parent-reported multi-national study of the impact of congenital and childhood onset myotonic dystrophy - JOHNSON, NICHOLAS E (Dev Med Child Neurol, 2015)
AIM: The frequency and impact of symptoms experienced by patients with congenital, childhood, and juvenile-onset myotonic dystrophy (CDM/ChDM/JDM) is not documented. This report identifies symptomatic areas with the greatest disease burden in an international population of patients with early-onset myotonic dystrophy type-1 (DM1). METHOD: We distributed surveys to parents of patients with CDM/ChDM/JDM. Patients with CDM/ChDM/JDM were members of the US National Registry of DM1 Patients and Family Members, the Canadian Neuromuscular Disease Registry, or the Swedish Health System. Surveys inquired about 325 symptoms and 20 themes associated with CDM/ChDM/JDM. Parents identified the importance of each symptom and theme to their affected child. The prevalence of each symptom and theme were compared across subgroups of patients. The statistical analysis was performed using Fisher’s exact and Kruskal–Wallis tests. RESULTS: One hundred and fifty parents returned surveys. The most frequently reported symptomatic themes in children were issues involving communication (81.7%) and problems with hands or fingers (79.6%). Problems with communication and fatigue were the issues that were reported to have the greatest impact on childrens’ lives, while 24.1% of children reported cardiac disorders and 15.8% had problems with anesthesia. INTERPRETATION: A range of symptoms contribute to the burden of disease faced by children with DM1. Many of these symptoms are under-recognized.